Enhanced recovery after surgery: Current status and future progress. Issue 4 (December 2021) - Rollins, Katie E.; Lobo, Dileep N.; Joshi, Girish P.
Abstract : Enhanced Recovery After Surgery (ERAS) pathways were first introduced almost a quarter of a century ago and represent a paradigm shift in perioperative care that reduced postoperative complications and hospital length of stay, improved postoperative quality of life, and reduced overall healthcare costs. Gradual recognition of the generalizability of the interventions and transferable improvements in postoperative outcomes, led them to become standard of care for several surgical procedures. In this article, we critically review the current status of ERAS pathways, address related controversies, and propose measures for future progress.